PRODUCTION OF THERMOSTABLE ENTEROTOXIN, HEMOLISINS, COLICIN AND FIMBRIAE IN STRAINS OF Escherichia coli ISOLATES OF PIGLETS WITH DIARRHEA OF SOUTHWEST PARANA - de BRITO, Benito Guimarães; TAGLIARI, Kelly Cristina; BERBEL, Milene Martins; FREIRE, Roberta Lemos (Scientia Agraria, 2003)
Escherichia coli is the most prevalent infectious agent in cases of diarrhoea in piglets. The virulence of this microrganism is determined by several determinants, specially fimbriae and toxins. In the present work, we analized 140 E. coli strains obtained from 82 suckling piglets and from 58 piglets with post-wening diarrhoea in farms located in the southwestern region of the State of Paraná, Brazil. The detection of the thermostable toxin was performed through the infant mouse test and colicin detection using the agar overlay method. The colonization factors were assayed through the microagglutination test, using different sources of red blood cells. In 37 (26,4%) and 26 (18,6%) of the samples, the presence of hemolisin and colicinogenic activity were detected, respectively. Thermostable enterotoxin was produced by 17 (12,1%) of the samples. Mannose resistant fimbriae was detected in 87 (62,1%) of the samples and 41 (29,3%) of the samples expressed type 1 fimbriae.